THE MANAGEMENT OF INTERNATIONAL COOPERATION IN SEBELAS MARET UNIVERSITY IN THE PERSPECTIVE OF GOOD UNIVERSITY GOVERNANCE - Febriani, Anis Fortina (Universitas Muhammadiyah Yogyakarta, 2018)
Objectives of this study are (1) to know the description of the management of international partnership in Sebelas Maret University (UNS) from the perspective of Good University Governance (2) to identify factors that affect the management of international partnership at the Sebelas Maret University. The location of this study conducted at the Sebelas Maret University. Type of the research is qualitative descriptive. Sources of data obtained from sources person, places and events or activity that was observed, and also from documents. The sampling technique of this study is purposive sampling. The data collection technique is by interview, observation and document review. Triangulation techniques was used to ensure the validity of the data. From the study of management of international partnership at the Sebelas Maret University shows several results (1) The principle of transparency has been accomplished on the mechanism that facilitates the public questions about the processes in governance but not in the application of the system of openness and the clearness and easiness to understand standardization all the processes of governance, and the mechanism for reporting and dissemination of information about aberrations action; (2) The principle of accountability has been accomplished in the distribution and grouping of work in accordance with the duties and functions principally but not in the understanding of the duties and functions as a manager and executor of cooperation, and accountability mechanisms of the budget; (3) The principle of responsibility is not yet implemented in the management of international cooperation; (4) the factors that support the implementation of Good University Governance are human resources and authority, while the inhibiting factor are the organizational structure and coordination systems